2014
DOI: 10.4331/wjbc.v5.i3.308
|View full text |Cite
|
Sign up to set email alerts
|

KAPtain in charge of multiple missions: Emerging roles of KAP1

Abstract: from conditional knockout mouse models reveal that KAP1-deficiency significantly impairs vital physiological processes, such as immune maturation, stress vulnerability, hepatic metabolism, gamete development and erythropoiesis. In this review, we summarize and evaluate current literatures involving the biochemical and physiological functions of KAP1. In addition, increasing studies on the clinical relevance of KAP1 in cancer will also be discussed. Key words: KRAB domain-associated protein 1; Transcriptional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 119 publications
1
95
0
Order By: Relevance
“…To identify a cellular target of LMP1-induced sumoylation that might be implicated in the progression of lytic replication, we first focused on a members of the tripartite motif family (KAP1). KAP1 can function as a transcriptional repressor (50,86), and the modification of KAP1 by SUMO at lysine 554, 575, 676, 750, 779, and/or 804 aids its repressive functions (54,(87)(88)(89)(90)(91)(92). Sumoylated KAP1 has been reported to bind to and repress Kaposi's sarcomaassociated herpesvirus (KSHV) lytic promoters (93); however, its function during the EBV life cycle remains unexamined.…”
Section: Lmp1 Ctar3 Is Not Essential For Viral Replicationmentioning
confidence: 99%
“…To identify a cellular target of LMP1-induced sumoylation that might be implicated in the progression of lytic replication, we first focused on a members of the tripartite motif family (KAP1). KAP1 can function as a transcriptional repressor (50,86), and the modification of KAP1 by SUMO at lysine 554, 575, 676, 750, 779, and/or 804 aids its repressive functions (54,(87)(88)(89)(90)(91)(92). Sumoylated KAP1 has been reported to bind to and repress Kaposi's sarcomaassociated herpesvirus (KSHV) lytic promoters (93); however, its function during the EBV life cycle remains unexamined.…”
Section: Lmp1 Ctar3 Is Not Essential For Viral Replicationmentioning
confidence: 99%
“…Several studies have revealed that the majority of KAP1 SUMOylation is balanced by the phosphorylation status of KAP1 and that the SUMOylation of KAP1 is required for its repressive function (14). Within or adjacent to the PB domain of KAP1, six Lys residues have been validated to be SUMOylation sites (45). To investigate the effect of KAP1 SUMOylation on KAP1-mediated E1B-55K SUMOylation, we generated KAP1-SUMO mutants with mutations at Lys676, Lys554, Lys779, and Lys804 (Fig.…”
Section: Kap1 Promotes E1b-55k Sumoylation While E1b-55k-sumo Conjugmentioning
confidence: 99%
“…Nrf2 and KAP1 inhibition has been associated with decreased proliferation and stress induction (45,46). We undertook a series of assays to determine if inhibition of these two proteins in the context of PEL resulted in growth inhibition.…”
Section: Brusatol Is a Novel Chemical Inhibitor Of Nrf2 That Mediatesmentioning
confidence: 99%